Effect of Different Wall Surface Coverage With Deltamethrin-Treated Netting on the Reduction of Indoor-Biting Anopheles Mosquitoes (Diptera: Culicidae). Issue 6 (11th June 2021) - Tainchum, Krajana; Bangs, Michael J; Sathantriphop, Sunaiyana; Chareonviriyaphap, Theeraphap
Abstract: Indoor residual spray with deltamethrin remains the most common tool for reducing malaria transmission in Thailand. Deltamethrin is commonly used to spray the entire inner surfaces of the walls to prevent mosquitoes from resting. This study compared the mosquito landing responses on humans inside three experimental huts treated with deltamethrin at three different extents of wall coverage (25%, 50%, and full coverage), with one clean/untreated hut serving as a control. There were no significant differences between the numbers of Anopheles mosquitoes landing in the 50% and full coverage huts, whereas, in comparison to both of these, there was a significantly greater number landing in the 25% coverage hut. This study demonstrates that varying the percent coverage of indoor surfaces with deltamethrin-treated netting influences the blood-feeding success of wild Anopheles, and our findings suggest that it may be possible to reduce the extent of insecticide surface treatment while maintaining equivalent mosquito avoidance action to that seen in fully treated structures.